Opportunities and Prospects for Implementation of the Effective Contract in the frame of Small and Medium Business ("Journal "U". Economy. Management. Finance.", 2017)
This article considers a rating system of labour assessment of the staff with a view to increasing the efficiency of working process organization. The manuscript provides analysis of the survey aimed at discovering which types of motivation are more important for company’s employees, prospects for possible stimulation of the staff for more effective activity, as well as improvement of organizational culture in whole.
Keywords: staff motivation; promotion; stimulation; economy; rating system of labour assessment; organizational structure